Polysaccharides As Viscosupplementation Agents: Structural Molecular Characteristics but Not Rheology Appear Crucial to the Therapeutic Response - Machado, Rita C.; Capela, Susana; Rocha, Francisco A. C. (Frontiers in Medicine, 2017)
Introduction: Most clinical studies and basic research document viscosupplementation (VS) in terms of effectiveness and safety, but only a few highlight its molecular mechanisms of action. Besides, there is generally focus on hyaluronic acid (HA) as being the most relevant polysaccharide to reach the clinical endpoints, attributing its effect mainly to its unique viscoelastic properties, related to a high molecular weight and gel formulation. Usually, studies do not approach the possible biological pathways where HA may interfere and there is a lack of reports on other biocompatible polysaccharides that could be of use in VS. Aim: We briefly review the main proposed mechanisms of action of intra-articular hyaluronic acid (IA-HA) treatment and discuss its effectiveness focusing on the role of rheological and intrinsic structural molecular properties of polysaccharides in providing a therapeutic effect. Methods: We conducted a literature search using PubMed database to find articles dealing with the mechanisms of action of IA-HA treatment and/or emphasizing how the structural properties of the polysaccharide used influenced the clinical outcomes. Discussion / Conclusion: HA is involved in numerous biochemical interactions that may explain the clinical benefits of VS, most of them resulting from HA - Cluster of differentiation (CD) 44 receptor interaction. There are other important aspects apart from the molecular size or the colloidal state of the IA-HA involved in VS efficiency that still need to be consolidated. Indeed, it seems that clinical response may be dependent upon the intrinsic properties of the polysaccharide, regardless of being HA, rather than to rheology, posing some controversy to previous beliefs.